Absent the archive : cultural traces of a massacre in Paris, 17 October 1961 - Brozgal, Lia Nicole, 1972- (Contemporary French and francophone cultures, 2020)
Absent the Archive is the first cultural history devoted to literary and visual representations of the police massacre of peaceful Algerian protesters. This corpus, or anarchive, includes a variety of cultural texts whose formal, diegetic, and discursive strategies represent the massacre and its erasure, its ""becoming invisible,"" and its afterlives as a trace, a memory, a sign.